PENERAPAN MODEL DISCOVERY LEARNING BERBANTU MEDIA PAPAN KANTOR UNTUK MENINGKATKAN PEMAHAMAN MATEMATIS MATERI FPB DAN KPK PADA SISWA KELAS IV SD NEGERI SENDANGMULYO 02 - Lailatul Hikmah; Aries Tika Damayani; Arfilia Wijayanti (Universitas PGRI Yogyakarta, 2020)
This Research Is Motivated By The Mathematical Value Of FPB and KPK material which is still below the KKM. This happens because in learning the teacher has not applied the model and media so that students' mathematical understanding is still lacking. This study aims to determine the effectiveness of the application of discovery learning model assisted by office board media to improve mathematical understanding of FPB and KPK material in grade IV SD Negeri Sendangmulyo 02.This type of research is quantitative research, with a pre-experimental research design in the form of One-Group. Pretest-Posttest. The population of this research is class IV SD Negeri Sendangmulyo 02, the sample taken by class IV B SD Negeri Sendangmulyo 02 with the number of students is 36, using the simple random sampling type Probability Sampling technique. In collecting data, researchers used several techniques including interviews, observation, documentation, and tests. The results showed that there were differences between the pretest and posttest scores. The average pretest score was 57.87 and the average posttest score was 76.62. This is evidenced by the calculation of the t test obtained ttable (2.030) and tcount (10.375). So tcount> ttable, meaning that Ho is rejected and Ha is accepted, and the percentage of students reaches 83%. This proves that the application of the discovery learning model assisted by office board media is effective in improving the mathematical understanding of FPB and KPK material in grade IV SD Negeri Sendangmulyo 02